2021
DOI: 10.5194/bg-18-4243-2021
|View full text |Cite
|
Sign up to set email alerts
|

Retracing hypoxia in Eckernförde Bight (Baltic Sea)

Abstract: Abstract. An increasing number of dead zoning (hypoxia) has been reported as a consequence of declining levels of dissolved oxygen in coastal oceans all over the globe. Despite substantial efforts a quantitative description of hypoxia up to a level enabling reliable predictions has not been achieved yet for most regions of societal interest. This does also apply to Eckernförde Bight (EB) situated in the Baltic Sea, Germany. The aim of this study is to dissect underlying mechanisms of hypoxia in EB, to identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Sea-bottom dissolved oxygen was inverse-correlated with sea-surface temperature at the global scale, and in the Baltic, Black Sea, North Sea, and Western Mediterranean, as inferable also by other studies; 63 , 64 , 78 , 83 85 …”
Section: Technical Validationsupporting
confidence: 84%
See 1 more Smart Citation
“…Sea-bottom dissolved oxygen was inverse-correlated with sea-surface temperature at the global scale, and in the Baltic, Black Sea, North Sea, and Western Mediterranean, as inferable also by other studies; 63 , 64 , 78 , 83 85 …”
Section: Technical Validationsupporting
confidence: 84%
“…These observations agree with those of other studies; 14 , 74 77 Sea-bottom salinity was generally positively correlated with sea-surface salinity in most seas except for the Black Sea, due to peculiar deep and shallow thermohaline dynamics 78 . It was also positively correlated with sea-bottom temperature in the Adriatic, Aegean, Bay of Biscay, and Levantine, as can also be inferred by other studies 79 82 ; Sea-bottom dissolved oxygen was inverse-correlated with sea-surface temperature at the global scale, and in the Baltic, Black Sea, North Sea, and Western Mediterranean, as inferable also by other studies; 63 , 64 , 78 , 83 85 Sea-ice concentration had no significant correlation with the other parameters. …”
Section: Technical Validationsupporting
confidence: 78%
“…Such offshore mixing has to be considered a highly influential process along the three stretches of coastline investigated in our study, in particular in the Eckernförde Bay. A recent study (Dietze & Löptien, 2021 ), which investigated offshore mixing in the Eckernförde Bay between 2000 and 2018 in high-resolution, showed highly variable water residence times (i.e. the time since the water entered the bay) and water ages (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified the wind direction as key driver for the intensity of variation. For instance, the abovementioned strong (north-easterly) winds that occurred in the week preceding our radon survey in the bay caused the water residence time in the inner bay to drop to under 10 days (Dietzen & Löptien, 2020 ). Wind-induced offshore mixing caused the discharged groundwater (enriched in radon) to be rapidly mixed with bay waters low in radon, resulting in less pronounced (or completely levelled-out) radon concentration anomalies close to the (physically identified) coastal SGD spots.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced OM degradation leads to elevated respiration rates, increased oxygen demand, consolidating developed hypoxia or even anoxia during certain times of the year (Lennartz et al, 2014). Sluggish deep-water renewal and restricted seafloor topography amplify local oxygen depletion (Dietze and Löptien, 2021). High benthic degradation rates under anoxic conditions support increased rates of SR and methanogenesis producing hydrogen sulfide and methane, respectively (Treude et al, 2005;Bertics et al, 2013;Maltby et al, 2018).…”
Section: Introductionmentioning
confidence: 99%